EFFECT OF INQUIRY LEARNING MODEL TRAINING AND CRITICAL THINKING SKILLS ON SCIENTIFIC KNOWLEDGE CLASS X - Envilwan Harefa; Motlan Sirait; Eva M. Ginting (Universitas Negeri Medan, 2016)
The aims of research were to analize: (1) Student’s skill proccess science by using inquiry training learning model better than direct intruction learning model; (2) Student’s skill process science who had under average better than above average category in scientific knowledge; and (3) the interaction between learning model and the level of scientific knowledge in fluencing student’s skill process science. The research was quasi-experimental research. The population of this research is all of thenth grade students of SMAN 3 Gunungsitoli. The sample of this researchconsist of grade with was taken by cluster random sampling were X2 and X3 class.The research instrument consisted of skill process science essay test and criticalthinking skills test data be analysed by using Two–way ANAVA. Result of theresearch showed that kill of the student science process (1) between inquiry training and direct intruction, where inquiry training better than direct intruction, (2) between group of student in the group of the students scientific knowledgeupon and under of mean, where scientific knowledge upon of mean better then scientific knowledge under of mean, (3) no interaction between inquiry training and scientific knowledge increased skill of student science process.